A novel alkylation process of benzene with CO2 and H2 over bifunctional ZnxCeyZrzO/Z5 catalyst. (15th October 2022) - Feng, Mingdi; Li, Yanchun; Liu, Ping; Wang, Junwen; Ge, Hui; Zhang, Kan; Duan, Donghong; Wang, Lian; Pei, XiangDong
Graphical abstract: The synergy between the two active sites in Zn3 Ce1 Zr3 O that the active hydrogen atoms provided by ZnO species hydrogenated the adsorbed CO2 at adjacent oxygen vacancy of cerium zirconium solid solution effectively improved the CO2 hydrogenation selectivity. While the HZSM-5 zeolite with moderate acidity was beneficial to the rapidly alkylation of methoxy intermediate with benzene. Coupling Znx Cey Zrz O with HZSM-5 could contribute to the well kinetic matching between CO2 activation and alkylation, thus affording an effective bifunctional catalyst Znx Cey Zrz O/Z5 for highly selective conversion of benzene with CO2 and H2 into toluene and xylene. Highlights: In situ alkylation process of benzene with CO2 and H2 to produce TX is proposed. The synergy in Znx Cey Zrz O promoted the CO2 hydrogenation kinetics. Znx Cey Zrz O/Z5 contribute to the well matching of CO2 activation and alkylation. The mechanism of the alkylation of benzene with CO2 and H2 is proposed. Abstract: Alkylation of benzene using CO2 and H2 to toluene and xylene (TX) can not only give value-added chemical products but also alleviate the greenhouse effect. The key to achieving this goal is to develop a highly efficient catalyst. Herein, a class of bifunctional catalysts containing series of Znx Cey Zrz O metal oxide and HZSM-5 was prepared and studied for the catalytic properties. Higher CO2 conversion and alkylation utilization were achieved using the Znx Cey O coupling with HZSM-5 compared to its counterpart ZnO and CeO2, revealing synergy between the ZnO and CeO2 . More strikingly, the Znx Cey Zrz O, synthesized by insertion of Zirconia (Zr) atoms into CeO2, can not only improve the concentration of oxygen vacancy but also facilitate CO2 adsorption. After coupling with HZSM-5, the alkylation utilization of CO2 was significantly improved and the unwanted CO selectivity was obviously reduced by hindering the RWGS reaction. The optimal bifunctional catalyst Zn3 Ce1 Zr3 O/Z5 showed alkylation utilization of 24%, unwanted CO selectivity of only 64% and the TX selectivity as high as 82%. In situ DRIFTS results confirmed that the methanol generated on the Znx Cey Zrz O metal oxide via the formate-methoxy intermediates mechanism was rapidly alkylated on HZSM-5 with benzene to produce TX.